Wayang Emas Di Bali Peradaban Budaya Hindu Nusantara - Linggih, I Nyoman (Kamaya: Jurnal Ilmu Agama, 2024)
The existence of wayang (shadow puppets) in the nusantara region dates back to 829 CE (907 AD), with its presence in Bali traced to 980 Saka (1058 AD). In modern times, the tradition of Wayang Emas (Golden Puppet) in Bali began in 2009. This study aims to explore the forms, functions, and meanings of Wayang Emas for the Hindu community in Nusantara. Data collection involved observations, literature studies, and interviews, analyzed through data reduction, data display, and conclusion drawing. The results indicate that Wayang Emas, crafted from pure yellow and white gold, is rooted in the Majapahit era. This unique tradition is linked to Prime Minister Gajah Mada's Palapa Oath, symbolizing the unification of nusantara under the Majapahit Kingdom in the 14th century. Wayang Emas exemplifies the advanced cultural and spiritual legacy of Hindu nusantara. It serves multiple functions: as an artistic expression, a medium of religious devotion, and a symbol of societal cohesion. Its sacred nature underscores the duality of physical and spiritual preservation, embodying cultural continuity while fostering faith in the oneness of God. In conclusion, Wayang Emas reflects the enduring influence of Majapahit Hindu culture and its ability to adapt to contemporary practices. As a tangible representation of unity and sanctity, it highlights the importance of safeguarding this heritage, ensuring its relevance for future generations while strengthening the spiritual and cultural identity of the Hindu community in nusantara.